1980
DOI: 10.2105/ajph.70.6.633
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and the high speed dental handpiece.

Abstract: RNs in the most neutral way, and themselves in between at all three stages. This finding tended to become even more pronounced over time. The two characteristics which emerge as most intense for all three occupations at all stages of the study are intelligence and competence. These findings suggest that the PA holds a positive image of the medical team members with whom he interacts. The attitude noted indicates that continued effective team work is highly probable and not likely to detract from the quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 8 publications
4
21
0
2
Order By: Relevance
“…[14][15][16][17] Another study compared the hearing status of Finnish dentists aged 33-42 years in 1973 and in 1988 and found that, even though the noise produced by turbines in 1973 was louder by 5-8.5 dB, the hearing thresholds were similar. 54 Thus, it seems there is a discrepancy between the continuing evolution and improvement of dental equipment, especially dental turbines [19][20][21][22] and progressive deterioration of hearing status in dental healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Another study compared the hearing status of Finnish dentists aged 33-42 years in 1973 and in 1988 and found that, even though the noise produced by turbines in 1973 was louder by 5-8.5 dB, the hearing thresholds were similar. 54 Thus, it seems there is a discrepancy between the continuing evolution and improvement of dental equipment, especially dental turbines [19][20][21][22] and progressive deterioration of hearing status in dental healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] However in almost all previous studies dentists did not experience higher HI risk than the general population. [14][15][16][17][18] This success was probably due to the technological improvement of dental equipment which considerably reduced the degree of environmental noise. [19][20][21][22] Nowadays, the noise levels generated by suction tubes, turbines, ultrasonic j o u r n a l o f d e n t i s t r y 4 0 ( 2 0 1 2 ) 8 2 1 -8 2 8 a r t i c l e i n f o Article history:…”
Section: Introductionmentioning
confidence: 99%
“…Even though, the exposure time of patients to noise in the dental clinic is limited to the treatment time, and may not lead to induced hearing losses, there are indications that dental anxiety, related to fear is aroused by dental equipment/instruments, tend to be a source of patient discomfort [2,3]. The sources of dental sounds that can pose as a potential hazard to hearing system of dentists and patients include high-speed turbine hand pieces, low-speed hand pieces, high-velocity suction, ultrasonic instruments and cleaners, vibrators, mixing devices such as amalgamators and model trimmers [4][5][6][7][8][9][10][11][12][13]. Occupational Safety and Health Administration (OSHA) has reported the daily permissible noise level of 85 decibels for 8 hours of continual exposure [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the audiogram of dentists in Saudi Arabia revealed that a significant number of dentists have a drop in the 4000 Hz audiogram frequency and 16.6% of dentists have tinnitus, 14.7% have difficulty in speech discrimination, 64% have difficulty in speech discrimination combined in a background noise (11). Pure tone audiometric evaluation among 80 physicians and 137 dentists revealed that dentists have a greater loss of hearing compared to physicians (12). Prevalence of hearing impairment among general dental practitioner and general medical practitioner in Italy is 30% and 14.8% respectively (13).…”
Section: Introductionmentioning
confidence: 99%